The complexity of the BATH words in Cardiff English - Mees, Inger M. (Linguistica (Ljubljana), 2017)
This article investigates how a small number of female speakers from Cardiff pronounce items belonging to the lexical set BATH. The data forms a subsample extracted from a longitudinal study on Cardiff English with recordings from 1977, 1990 and 2011. The BATH set comprises items (e.g., chance, bath) whose citation forms contain the TRAP vowel /a/ in General American but the PALM vowel /(...)/ in British RP. In other accents of English, including Cardiff English, the lexical distribution of the items is often less straightforward, with some items taking PALM while others take TRAP. The situation is particularly complex in Cardiff as the realisations of TRAP and PALM may sound very similar, both having a front vowel quality; furthermore, TRAP may be halflong. Consequently, it can be difficult to determine which of the vowels is selected. We analyse the vowels (both vowel quality and duration) of 11 (five in 2011) working and middle class informants who recorded a reading passage containing seven BATH words at all three points in time. In addition, we study a word list comprising 34 items read by the same speakers in 1990 and 2011. The vowels were subjected to both auditory impressionistic and acoustic analyses. We attempt to establish the social significance attached to the different pronunciations and also to discover if phonological context plays a role for the choice of vowel.
Keywords: angleščina; besedišče "BATH"; Cardiff; English; izgovorjava; samoglasniki